THE STRATEGIC PLAN OF UNIVERSITY IN FACING CHALLENGES OF INDUSTRIAL REVOLUTION 4.0 - hapsari Shinta Citra Puspita Dewi; Nurhasan Nurhasan; Made Pramono; Martadi Martadi; Erta Erta (Jurnal Pendidikan (Teori dan Praktik), 2020)
Industrial Revolution 4.0, as one of the main paradigms of the modern economy, requires higher education to improve in the face of this trend. Surabaya State University (Unesa) emphasizes the development of human resources (HR) as the main target of internal development in order to deal with industry 4.0. The academic community is encouraged to be sensitive to technology, by increasing intellectual capacity through civilization, training, competition, and / or schools. The study aims to identify the readiness of Unesa in facing challenges of Industry Revolution 4.0. The implication of research is to enrich the education management research about linking strategy between higher education and industry demand. The result of research implies that Unesa has moderate readiness in facing the challenges of Industry Revolution 4.0 by deepening intellectual capacity in the IT field through the improvement of campus facilities and infrastructure, and procurement of new learning technologies. Networking is also becoming a useful strategy in linking HR with the IT world related to Industry 4.0. Such a strategic effort under the prevailing laws and regulations enable Unesa to advance in pioneering the development of industry 4.0 on campus, especially for creating qualified graduates.